Student centered: Characteristics of the new generation - Sergeyeva, Tetyana Viktorivna; Ushakova, S.; Rachkovskyi, O. (BoScience Publisher, 2021)
The article is devoted to the problem of reorientation of university education from a traditional subject-centered to innovative student-centered learning. Such transformation requires the study of the characteristics of all participants in educational interaction: students - teachers - educational environment. Since the student is the system-forming factor in this interaction, the study of the characteristics of modern students becomes especially relevant. The article presents the results of the study of semantic, cognitive and personal characteristics of modern students with recommendations for the use of both positive and negative trends in the effective organization of the educational process.
Keywords: student-centered learning; modern students; semantic; cognitive; personal characteristics